DOES LOAN RESTRUCTURING POLICY AFFECT CREDIT RISK? THE CASE OF INDONESIAN BANKING FIRMS - Ananda, Feni; Budianto, Risky (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
One of the risks faced by banks when carrying out the intermediation function is credit risk, which arises due to debtors who fail to fulfill their obligations. To mitigate the impact of this increased risk, banks and regulators implement loan restructuring policies. This study was conducted to examine the effect of loan restructuring policies on credit risk as measured by the Non-Performing Loan ratio. The population used is banking companies listed on the Indonesia Stock Exchange (IDX) in 2020-2024 with a sample of 200. Panel data regression analysis was carried out using the Generalized Least Squares (GLS) model and utilizing the EViews 13 software. The study's results demonstrate a positive correlation between the loan restructuring policy and an increase in credit risk. In addition, LDR and BOPO as control variables could increase the credit risk, while the bank size indicator which is total assets could help to reduce the credit risk. This result indicates that although restructuring is intended to ease the burden on debtors and reduce non-performing loans, its implementation can create a moral hazard thereby increasing credit risk. Salah satu risiko yang dihadapi perbankan ketika menjalankan fungsi intermediasi adalah risiko kredit, dimana timbul akibat debitur yang gagal dalam memenuhi kewajibannya. Untuk memitigasi dampak peningkatan risiko ini, bank dan regulator menerapkan kebijakan restrukturisasi pinjaman. Penelitian ini dilakukan untuk menguji pengaruh kebijakan restrukturisasi pinjaman terhadap risiko kredit yang diukur dengan rasio Non-Performing Loan. Populasi yang digunakan merupakan perusahaan perbankan yang terdaftar di Indonesia Stock Exchange (IDX) tahun 2020-2024 dengan jumlah sampel sebanyak 200. Analisis regresi data panel dilakukan dengan model Generalized Least Squares (GLS) dan memanfaatkan software EViews 13. Hasil penelitian mendemonstrasikan adanya korelasi positif antara kebijakan restrukturisasi kredit dan peningkatan risiko kredit. Disisi lain, LDR dan BOPO yang bertindak sebagai variabel kontrol dapat meningkatkan risiko kredit, sementara indikator ukuran bank yakni total aset membantu menurunkan risiko kredit. Hasil ini menandakan bahwa meskipun restrukturisasi dimaksudkan untuk meringankan beban debitur dan menekan kredit bermasalah, implementasinya dapat menimbulkan moral hazard sehingga meningkatkan risiko kredit.